The Interpretive Variability of Cervical Biopsies and Its Relationship to HPV Status. (June 2015) - Stoler, Mark H.; Ronnett, Brigitte M.; Joste, Nancy E.; Hunt, William C.; Cuzick, Jack; Wheeler, Cosette M.
Abstract : Diagnostic interpretation of a cervical biopsy is a key element in the decision to treat or not to treat a woman with an abnormal screening test. This study assesses the variability of these diagnostic interpretations on a population basis using the New Mexico HPV Pap Registry database. An experienced panel of gynecologic pathologists reviewed a stratified random sample of 6272 biopsies, which was then extrapolated to the entire population of 21, 297 biopsies read by the community pathologists. Diagnoses by the community and panel pathologists were compared, and paired diagnoses were correlated with positivity for human papillomavirus 16 (HPV16) and any high-risk HPV as objective measures of progressive potential. Panel agreement with the community diagnosis was 38.2% for cervical intraepithelial neoplasia grade 1 (CIN1), 38.0% for CIN grade 2 (CIN2), 68.0% for CIN grade 3 (CIN3), and 70.6% for cancer. The κ value was 0.46 overall but higher for dichotomous categorization based on CIN2 or CIN3 cutoff points (0.68 and 0.67, respectively). On a population basis, there were fewer CIN1 and more negative diagnoses in the panel review but similar proportions of CIN2 and CIN3. HPV16 and high-risk HPV positivity increased with disease severity, but panel review did not improve the correlation of higher-grade disease with these objective measures. In this population-based study of the variability in cervical diagnoses, we noted significant variability in the community and panel diagnoses, especially for CIN2, the threshold for excisional treatment. New biomarkers are needed to more accurately stratify precursor lesions according to their malignant potential. Abstract : Supplemental Digital Content is available in the text.